A systematic review of reported outcomes and outcome measures in randomized trials evaluating surgical interventions for posterior vaginal prolapse to aid development of a core outcome set. Issue 3 (12th January 2020) - Lourenço, Thais R.M.; Pergialiotis, Vasilis; Durnea, Constantin M.; Elfituri, Abdullatif; Haddad, Jorge M.; Betschart, Cornelia; Falconi, Gabriele; Nygaard, Christiana C.; Bergstrom, Lina; Pattel, Mittal; Doumouchtsis, Stergios K.; ,
Abstract: Background: Recent systematic reviews have demonstrated wide variations on outcome measure selection and outcome reporting in trials on surgical treatments for anterior, apical and mesh prolapse surgery. A systematic review of reported outcomes and outcome measures in posterior compartment vaginal prolapse interventions is highly warranted in the process of developing core outcome sets. Objective: To evaluate outcome and outcome measures reporting in posterior prolapse surgical trials. Search strategy: We searched MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials (CENTRAL). Selection criteria: Randomized trials evaluating the efficacy and safety of different surgical interventions for posterior compartment vaginal prolapse. Data collection and analysis: Two researchers independently assessed studies for inclusion, evaluated methodological quality, and extracted relevant data. Methodological quality, outcome reporting quality and publication characteristics were evaluated. Main results: Twenty‐seven interventional and four follow‐up trials were included. Seventeen studies enrolled patients with posterior compartment surgery as the sole procedure and 14 with multicompartment procedures. Eighty‐three reported outcomes and 45 outcome measures were identified. The most frequently reported outcomes were blood loss (20 studies, 74%), pain (18 studies, 66%) and infection (16 studies, 59%). Conclusions: Wide variations in reported outcomes and outcome measures were found. Until a core outcome set is established, we propose an interim core outcome set that could include the three most commonly reported outcomes of the following domains: hospitalization; intraoperative, postoperative urinary, gastrointestinal, vaginal and sexual outcomes; clinical effectiveness. PROSPERO: CRD42017062456. Abstract : This systematic review evaluated the variation in reported outcomes and outcome measures for posterior vaginal wall prolapse interventions.